Optimizing human capital: Strategies and challenges in Indonesia's HR landscape - Kasbuntoro, Kasbuntoro (Journal of Economics and Business Letters, 2022)
This research investigates the evolving landscape of Human Resource (HR) management in Indonesia, highlighting strategic approaches and identifying key challenges within the context of globalization and technological advancements. Indonesia, characterized by its diverse workforce and dynamic economy, faces unique HR management challenges, including talent acquisition, employee retention, and the integration of technology in HR practices. Utilizing a comprehensive literature review and analysis of current practices, this study examines effective HR strategies implemented by Indonesian companies and assesses their impact on organizational performance and employee satisfaction. Furthermore, it explores the role of cultural factors in shaping HR management in Indonesia and the implications of digital transformation for HR practices. The findings suggest a critical need for Indonesian businesses to adopt more integrated and adaptive HR strategies that align with global trends while considering local cultural nuances. This study contributes to the broader discourse on HR management in emerging economies and provides insights for policymakers, business leaders, and HR professionals aiming to navigate Indonesia's complex HR landscape.